Forearm substrate utilization during exercise after a meal containing both fat and carbohydrate. - Griffiths, A; Humphreys, S; Clark, M; Frayn, K (1994)
1. Whilst the provision of exogenous carbohydrate has been shown to be beneficial to endurance exercise performance, little attention has been paid to the possibility of dietary manipulation of the availability of fat. 2. Ten normal subjects were studied on two occasions: after an overnight fast (postabsorptive state) and after a meal containing 80 g of fat and 80 g of carbohydrate (fed state). Forearm substrate exchange was studied during 60 min of isometric forearm exercise (5 s contraction, 5 s relaxation). 3. In the fed state concentrations of plasma triacylglycerol (1510 +/- 150 versus 850 +/- 80 mumol/l, P < 0.01), blood ketone bodies (151 +/- 21 versus 80 +/- 10 mumol/l, P < 0.01) and plasma insulin (17 +/- 3 versus 7 +/- 1 m-units/l, P < 0.01) were elevated compared with the postabsorptive state; plasma glucose and non-esterified fatty acid concentrations were not significantly different. 4. Forearm blood flow and O2 consumption each increased about 6-fold during exercise, with no differences between the two nutritional states. The potential contribution of individual substrates to forearm O2 consumption (a calculation which is independent of blood flow) was assessed: for triacylglycerol it was significantly greater in the fed state (P < 0.01). The sum of the potential contributions of triacylglycerol, non-esterified fatty acids, glucose and ketone bodies to forearm O2 consumption was significantly greater, both before and during exercise, in the fed than in the postabsorptive state (P < 0.05), implying the sparing of endogenous (forearm) fuels. 5. These studies highlight the potential for manipulation of substrate supply during exercise by feeding meals containing both carbohydrate and fat.